Phenotypic Alterations in Hippocampal NPY- and PV-Expressing Interneurons in a Presymptomatic Transgenic Mouse Model of Alzheimer’s Disease - Mahar, Ian; Albuquerque, Marilia Silva; Mondragon-Rodriguez, Siddhartha; Cavanagh, Chelsea; Davoli, Maria Antonietta; Chabot, Jean-Guy; Williams, Sylvain; Mechawar, Naguib; Quirion, Rémi; Krantic, Slavica (Frontiers in Aging Neuroscience, 2017)
Interneurons, key regulators of hippocampal neuronal network excitability and synchronization, are lost in advanced stages of Alzheimer’s disease (AD). Given that network changes occur at early, presymptomatic, stages we explored whether alterations of interneurons also occur before amyloid-beta (Aβ) accumulation. Numbers of neuropeptide Y (NPY) and parvalbumin (PV) immunoreactive (-IR) cells were decreased in the hippocampus of 1 month-old TgCRND8 mouse AD model in a sub-regional-specific manner. The most prominent change observed was a decrease in the number of PV-IR cells that selectively affected CA1/2 and subiculum, with the pyramidal layer of CA1/2 accounting almost entirely for the reduction in number of hippocampal PV-IR cells. Because PV neurons were decreased selectively in CA1/2 and subiculum and given that they are critically involved in the control of hippocampal theta oscillations, we then assessed intrinsic theta oscillations in these regions after a 4-amynopyridine (4AP) challenge. This revealed increased theta power and population bursts in TgCRND8 mice compared to non-transgenic controls, suggesting a hyperexcitability network state. Taken together, our results identify for the first time AD-related alterations in hippocampal interneuron function as early as at 1 month of age. These early functional alterations occurring before amyloid deposition may contribute to cognitive dysfunction in AD.